Diversity of Residential Mobility Dynamics towards Metropolitan Inner Cities in Andalusia. - Torrado-Rodríguez, José Manuel (Revista de Estudios Andaluces, 2017)
Residential movements towards metropolitan inner cities are movements which have been paid little attention to, despite the key role that they play in the incipient stages, as well as in the more advanced, of metropolitan development. Moreover, when they have been studied they have tended to be understood as unique, undifferentiated reality. This work, using census data from 1991 and 2011, and based on a complex delimitation of the Andalusian metropolitan areas, contributes to the differentiation and conceptualization of centralization movements, proving two fundamental facts: first, that the role played by these movements in different stages of metropolitan development is different, and second, that their characteristics, and therefore their consequences in the transformation of the city, differ substantially according to the greater or lesser integration in the metropolitan processes of their origin’s zones.